Factors associated with postpartum hemorrhage in selected Southern Oromia hospitals, Ethiopia, 2021: an unmatched case-control study - Negesa Beyene, Belda; Jara Boneya, Dube; Gelchu Adola, Shiferaw; Abebe Sori, Seboka; Dinku Jiru, Hirut; Sirage, Nurye; Awol, Abdurazak; Melesse, Girma Tufa; Wayessa, Zelalem Jabessa; Jemalo, Ahmedteyib; Kebede, Abebaw; Eshetu, Derese; et al. (Frontiers in Global Women's Health, 2024)
Background: Around one-fourth of maternal deaths worldwide are attributed to hemorrhage.One of the prevalent types of maternal hemorrhage is postpartum hemorrhage. In spite of this, there is very little data on postpartum hemorrhage. Thus, the intention of this study was to determine factors associated with postpartum hemorrhage among mothers who gave birth in the selected Southern Oromia hospitals in Ethiopia.Methods: An institutional-based, unmatched case-control study was employed on a sample of 333 (83 cases and 250 controls) mothers who gave birth from March 1-30, 2021. Standardized and pretested check-lists were used to retrieve data from patients' cards, delivery registration, and operation registration logbooks. Epi Data Version 3.1 was used to enter data, while SPSS Version 25 was used for analysis. Multi-variable logistic regressions were used to identify the determinants of postpartum haemorrhage with a 95% confidence interval and p-value less than 0.05.